Micro-scale hydrocarbon distribution in organic-rich shales: A case study in the Union Springs Formation, Marcellus Subgroup (USA) - Fosu-Duah, E. (Slovnaft VURUP a.s, 2017)
The high economic pressures have shifted the interest in shale resource plays from gas to gas condensates and oil. Geochemically, this is a shift in research perspective from mere knowledge of the organic carbon content of the host rock to the kind, maturity, and extent of heterogeneities in the distribution of the organic components of the shale. This is critical due to the direct relationship between organic carbon and gas storage, transport and deliverability. To investigate the extent of hetero-geneities in the hydrocarbon distribution, a combination of Fourier transform infrared spectroscopy, total organic carbon analysis, and ultra-violet infrared spectroscopy were utilized. Shale for the study was sampled from the Union Springs Formation of the Marcellus Subgroup in Pennsylvania. Data analyses from a 10 x 10 cm grid locations show a range of total organic carbon values from 7.51 to 8.96 and an average of 8.13. Every sample was dominated by aromatic hydrocarbons with E4: E6 values ranging from 2.96 and 3.66. In terms of functional groups, sporadic changes in hydrocarbon bonds were reported. These ranged from the presence of methyl or methylene a/symmetric aliphatic hydrocarbons to aromatic combination C-H, C=C stretching bonds at relatively short intervals. Heterogeneities in the kinds of hydrocarbon reported and their distributions were attributed to the variations in the paleoenvironmental redox conditions, source material, complex depositional history, temporal variations and varying sedimentation rates.